Is the trajectory of European Union environmental policy less certain?. Issue 2 (23rd February 2019) - Zito, Anthony R.; Burns, Charlotte; Lenschow, Andrea
ABSTRACT: The core themes and research questions of this volume, centred on the nature of environmental policy change in the European Union (EU), are laid out. An original heuristic framework to capture different dimensions, mechanisms and processes of policy change is presented. In order to contextualise the current situation, where EU policy scope has reached maturity and faces an uncertain future trajectory, EU environmental politics is divided into particular eras, looking closely at the nature of change in each period. This volume interrogates the extent to which change has occurred, the conditions or context within which it did/did not take place and the implications arising from stasis or change. The contributions to the volume are introduced and placed into the context of the broader trajectory of EU environmental policy.